PHYTOCHEMICAL ANALYSIS OF CALLUS TWO VARIETIES ORTHOSIPHON ARISTATUS (BLUME) MIQ ON MURASHIGE AND SKOOG MEDIA: A STRATEGIC STEP OF SECONDARY METABOLITE PRODUCTION - FARAMAYUDA, FAHRAUK; MARIANI, TOTIK SRI; ELFAHMI; SUKRASNO (International Journal of Applied Pharmaceutics, 2021)
Objective: The research aimed to provide new information regarding the secondary metabolites content of purple and white-purple Orthosiphon aristatus (Blume) Miq. callus, which can then be used as a basis for developing towards cell suspension and ultimately producing secondary metabolites using bioreactors. Methods: Callus induction of two varieties of O. aristatus were performed by inoculating sterile leaf explants grown on Murashige and Skoog basal media supplemented with 2,4-dichlorophenoxyacetis acid 0.4 ppm. The secondary metabolites were analysed and quantified using high-performance liquid chromatography with gradient elution. Results: The results showed the growth of callus two varieties of O. aristatus in growth media MS with 2,4-D 0.4 ppm. Rosmarinic acid content in the acetone extract of the purple variety callus was 1.28% w/w, and the white-purple variety was 2.22% w/w. Conclusion: This study could form the basis for the development of rosmarinic acid production by In vitro culture modification.